Fleas (Insecta-Siphonaptera) of Chile: a review - Beaucournu, Jean-Claude; Moreno, Lucila; González-Acuña, Daniel (Zootaxa, 2014)
This study presents a revision of the fleas (Siphonaptera) in Chile, gathered from 1993–2013 in response to a request to update our knowledge of the fauna of this country, as catalogued by Beaucournu & Gallardo in 1991 and 1992. For each taxon we give the depository of the type, the main references concerning it, its general distribution, particularly in Chile, and its known hosts, mainly in this country. Our review of the existing literature on fleas of Chile gives information on a total of 8 families, 11 subfamilies, 31 genera, 9 subgenera and 112 species (with 11 subspecies). The hosts are represented by 21 families of mammals (91 species) and 16 of birds (27 species). In addition we present 21 new reports of fleas for Chile and 165 new localities.